Risk of selected gastrointestinal toxicities associated with poly (ADP-ribose) polymerase (PARP) inhibitors in the treatment of ovarian cancer: a meta-analysis of published trials - Liu Y; Meng J; Wang G (Drug Design, Development and Therapy, 2018)
Yongping Liu, Jun Meng, Guichan Wang Department of Gynecology, Obstetrics, Yuhuangding Hospital, Yantai, Shandong Province, People’s Republic of China Aims: We aimed to comprehensively assess the risk of gastrointestinal toxicities associated with poly (ADP-ribose) polymerase inhibitors (PARPis) in the treatment of ovarian cancer patients.Materials and methods: We searched several databases for relevant trials. Eligible studies included prospective Phase II and III trials of ovarian cancer patients on the four PARPis (olaparib, veliparib, niraparib and rucaparib), describing events of nausea, vomiting, diarrhea, and constipation. Summary incidence, relative risk (RR), and 95% CIs were calculated employing fixed- or random-effects models.Results: A total of 2,286 ovarian cancer patients from 12 trials were included for analysis. Our results showed that summary incidences of all-grade gastrointestinal events in ovarian cancer patients were nausea 68.8% (95% CI, 63.5%–73.6%), vomiting 36.2% (95% CI, 30.9%–41.8%), diarrhea 25.3% (95% CI, 21.2%–29.8%), and constipation 25.3% (95% CI, 17.9%–34.5%). The RRs of all-grade nausea, vomiting, diarrhea, and constipation were 2.00 (95% CI: 1.79–2.24; P<0.001), 2.12 (95% CI: 1.75–2.58; P<0.001), 1.20 (95% CI: 1.01–1.44; P=0.044), and 1.20 (95% CI: 0.88–1.80; P=0.21); respectively. While, the RRs of high-grade nausea, vomiting, diarrhea, and constipation were 3.74 (95% CI: 1.50–9.36; P=0.005), 2.81 (95% CI: 1.17–6.74; P=0.02), 0.56 (95% CI: 0.22–1.43; P=0.23), 0.92 (95% CI: 0.34–2.49, P=0.87); respectively.Conclusion: Our study suggests that the risk of all-grade gastrointestinal toxicities associated with PARPis, excepting constipation, is significantly increased in ovarian cancer patients. And the use of PARPis significantly increased the risk of developing high-grade nausea and vomiting, but not for diarrhea and constipation. Close clinical monitoring is recommended when administering these drugs. Keywords: poly (ADP-ribose) polymerase inhibitors, gastrointestinal toxicities, clinical trials, meta-analysis, targeted agents, gynaecological tumors, systematic review